1976
DOI: 10.1159/000221937
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Nosocomially Significant, Multiple Drug-Resistant Strain of <i>Serratia marcescen</i><i>s</i>

Abstract: A multiple drug-resistant strain of Serratia marcescens (bacteriocin type 18) was isolated from three clinical patients. The isolates were found to carry a conjugally nontransferable, nonmobilizeable resistance plasmid (R-plasmid) with resistance-(r-)determinants against ten antimicrobial drugs: ampicillin, carbenicillin, chloramphenicol, gentamicin, kanamycin, neomycin, streptomycin, tobramycin, triple sulfonamides, cotrimoxazole, and – possibly – nalidixic acid, as determined with exposure to ‘curing’agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Variant No. 65 (SE 154) spontaneously had lost 12 r-markers on a previous occasion [18]. The confirmatory MICs of CHLOR, NA, and TMP for these spontaneously 'cured' variants are shown in table VI.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Variant No. 65 (SE 154) spontaneously had lost 12 r-markers on a previous occasion [18]. The confirmatory MICs of CHLOR, NA, and TMP for these spontaneously 'cured' variants are shown in table VI.…”
Section: Resultsmentioning
confidence: 88%
“…Since October, 1973, a multiple-drug-resistant strain of S. marcescens (bacteriocin type 18), which was found to be resistant against all currently available chemo therapeutic agents except amikacin, acquired nosocomial significance, in that so far (July, 1976) this particular strain had been recovered from various clinical specimens derived from 18 patients in four different uni versity hospitals at Erlangen. A recent report [18] presented evidence that the R-plasmid of this strain is nonconjugative and nonmobilizable. Furthermore, based on 'curing' data that had been obtained with ethidium bromide, acridine orange, and sodium dodecyl sulfate, and on the high rate of spontaneous loss of resistance markers (r-markers), it was tenta tively concluded that this particular R-plasmid-mediated resistance against ampicillin, carbenicillin, chloramphenicol, gentamicin, kanamycin, neomycin, streptomycin, tobramycin, triple sulfonamides, cotrimoxazole, and -possibly -nalidixic acid.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Early isolates of this species were susceptible to carbenicillin (Cb) and gentamicin (Gm) (8), the latter being considered one of the most useful antibiotics against this species (4,7). Recently, however, a number of clinical isolates of S. marcescens have been described that are resistant to one or both of these antibiotics (10,14,16). In several cases, such resistance was found to be transferable and presumably associated with R factors (11,14).…”
mentioning
confidence: 99%